Emotion‐related impulsivity and rumination: Unique and conjoint effects on suicidal ideation, suicide attempts, and nonsuicidal self‐injury across two samples. Issue 4 (7th March 2022) - Johnson, Sheri L.; Robison, Morgan; Anvar, Sarah; Swerdlow, Benjamin A.; Timpano, Kiara R.
Abstract: Introduction: Rumination and emotion‐related impulsivity predict suicidal ideation, suicide attempts, and nonsuicidal self‐injury (NSSI). Because rumination and emotion‐related impulsivity, though, are highly correlated, we consider their unique vs. conjoint influence on suicidal ideation and self‐harm. Method: Across two samples of adults ( N 's = 171 and 191), we examined how rumination and emotion‐related impulsivity relate to suicidal ideation, suicide attempts, and NSSI. We assess the more general process of repetitive negative thinking and the more specific process of suicide‐related rumination. Participants completed the Three‐Factor Impulsivity Index and the self‐report Columbia‐Suicide Severity Rating Scale. Those in sample 1 completed the Perseverative Thinking Questionnaire and the Deliberate Self‐Harm Inventory, and those in Sample 2 completed the Suicide Rumination Scale. Results: Emotion‐related impulsivity and both forms of rumination showed robust bivariate correlations with suicidal ideation, suicide attempts, and NSSI. Neither rumination or impulsivity related to suicide attempts controlling for ideation or to NSSI. In multivariable analyses, emotion‐related impulsivity but not general rumination was tied to suicidal ideation. In contrast, suicide‐related rumination was more directly tied to suicidal ideation than was impulsivity. Conclusions: Findings provide support for a more nuanced approach to the forms of impulsivity and rumination related to suicidal ideation.